Prosecutorial Discretion and the Imposition of Mandatory Minimum Sentences - Ulmer, Jeffery T. (Journal of research in crime and delinquency, 2007)
In Pennsylvania, the imposition of mandatory minimum sentences presents an important opportunity to examine relatively "pure" prosecutorial discretion over sentencing outcomes. The authors present a multilevel analysis of the prosecutorial decision to apply a mandatory minimum among mandatory-eligible offenders sentenced for drug crimes or as repeat, "three-strikes" offenders. They find that prosecutors' decisions to apply the mandatory minimum are significantly affected by the type and characteristics of offenses and guideline sentence recommendations, prior record, mode of conviction, and gender. They also find that Hispanic males are more likely to receive mandatory minimums and that Black-White differences in mandatory application increase with county percentage Black. The authors frame and interpret their analysis and findings in light of the uncertainty reduction theory of prosecutorial discretion, the view of courts as communities, and an integrative focal concerns perspective on criminal justice decision-making. [ABSTRACT FROM AUTHOR]